Kebijakan Insentif Pajak dan Sosialisasi Pajak terhadap Peningkatan Penerimaan Pajak di Masa Pandemi Covid-19 Tahun 2021 - Dyah Oktaviani; Anik Yuliati (IPM2KPE, 2022)
This study aims to empirically identify and analyze the effect of tax incentive policies and tax socialization on increasing tax revenue during the Covid-19 pandemic. This research method is descriptive quantitative. The population used in this study is all individual taxpayers registered at KPP Pratama Surabaya Gubeng. Sampling was carried out using a non-probability sampling technique, namely incidental sampling and using Roscoe's theory in sampling. Analysis of the existing data in this study is to use multiple linear regression analysis. The results showed that the F test value (simultaneous) on the tax incentive policy variable (X1) and tax socialization (X2), namely Fcount, was 20,023> Ftable with a sig value of <0.05. Ftable for the probability of 0.05 at the level of 2;78 which is equal to 3.11. In conclusion, tax incentive policies, and tax socialization have a simultaneous effect on tax revenue at KPP Pratama Surabaya Gubeng during the Covid-19 pandemic in 2021. Keywords: Tax Incentive Policy, Tax Revenue, Tax Socialization